THE IMPORTANCE OF THE USE OF ROLEPLAYING METHODS IN TEACHING ENGLISH SPEAKING - Rashidova Ruxshonaxon Rustamjon qizi (Western European Studies, 2024)
This article provides information about role playing methods in teaching English speaking lessons. The role playing method is a very effective way to teach the speaking method of the English language, and by involving students in simulated real-life situations, role playing helps students to practice and improve their speaking and communication skills in a meaningful context.
Keywords: Speaking; role playing; communicative teaching metods